Novel nutraceutical supplements with yeast β-glucan, prebiotics, minerals, and Silybum marianum (silymarin) ameliorate obesity-related metabolic and clinical parameters: A double-blind randomized trial - Nehmi-Filho, Victor; Santamarina, Aline Boveto; de Freitas, Jéssica Alves; Trarbach, Ericka Barbosa; de Oliveira, Daniela Rodrigues; Palace-Berl, Fanny; de Souza, Erica; de Miranda, Danielle Araujo; Escamilla-Garcia, Antonio; Otoch, José Pinhata; Pessoa, Ana Flávia Marçal (Frontiers in Endocrinology, 2023)
Purpose: It is known that obesity has a multifactorial etiology that involves genetic and environmental factors. The WHO estimates the worldwide prevalence of 1.9 billion overweight adults and more than 650 million obese. These alarming data highlight the high and growing prevalence of obesity and represent a risk factor for the development and aggravation of other diseases. Like as nonalcoholic fatty liver disease (NAFLD) is frequently considered the hepatic outcome of type 2 Diabetes. The use of non-pharmacological therapies like new food supplements, nutraceuticals, and natural integrative therapies has grown compared to conventional medications. The main hypothesize is that the novel supplement might improve and supply essential nutrients providing an improvement of fatty liver diseases, through metabolic and endocrine pathways. Methods: Sedentary Volunteers (woman and man) with BMI ≤34.9 were divided into two groups: Novel Nutraceutical Supplement_(S) (n=29) and Novel Nutraceutical Supplement (n=30). Volunteers took two capsules in the morning and more two capsules in the evening of the Novel Nutraceutical Supplements. Neither nutritional intervention was performed during the study period. The data (anthropometrics and anamneses) and harvest blood (biochemistry and hormonal exams) were collected from the volunteers at three different times: baseline time (day zero-T0), day 90 (T90), and day 180 (T180) post-supplementation. Results: In the anthropometrics analysis, the Waist-to-Height Ratio (WHtR) and Waist-to-Hip Ratio (WHR) seem to slightly decrease alongside the supplementation period with both Novel Nutraceutical Supplements; thus, (AST)/ (ALT) ratio (AAR) biomarker from NAFLD, and cortisol and TSH endocrine hormones in 90- and 180 days post-supplementation. Conclusions: In a condition associated with sedentary and no nutritional intervention, the Novel Nutraceutical Supplements demonstrated the ability to be a strong and newfangled tool to improve important biomarkers associated with obesity.